EFFECT OF SAND CONTAMINANT IN CRUDE OIL PIPELINE - MOHAMAD NASRI, MOHAMAD NAAIM (2018)
Sand Contamination in crude oil pipeline can lead to erosion thus affect the transmission of hydrocarbon products. Based on most reported cases, the most vulnerable parts in transmission pipeline is 90o elbow pipe because of many factors that can contribute to erosion rate. This project highlights on the effects of the unwanted solid particles such as sand inside a 90o elbow pipeline in terms of the velocity of the flow, the size of the particle, the mass flow rate of the particle. In addition, simulations on the reaction of the particles are conducted through ANSYS; a software designed to simulate variations of simulations with selected parameters. Mesh study has been done to ensure a proper mesh is selected for the simulation thus to gain accurate result. A simple 90o pipeline model has been created. There are nine simulations; three simulations for each factor to compare the results thus to conclude the effect for each factor toward erosion rate of 90o bend pipe. Evaluation has been made after each of the simulations to verify the reliability of the simulation. The behavior of the particles inside the 90o elbow pipeline is shown in results and discussion section including the effects of velocity of the flow on the erosion rate, the effects of size of the particles on erosion rate and the effects of mass flow rates of the particles on erosion rate. These results have been compared with a research paper to ensure the validation of the result. Besides that, a Computational Fluid Dynamic has been developed and simulations on difference parameters that affect erosion rate has been done. Based on the simulations, it shows that when the velocity flow is high, the size of the particles in diameter is large and the mass flow rate is high, the higher the erosion rate inside the elbow pipe. These result is shown in results and discussion section in this report. Recommendations on the possible solution for the erosion is included in this project.